Construcción De Las Nuevas Masculinidades En La Ciudad De Armenia Vista Desde La Teoría Simbólica (2013)
Man, as part of the unity of mankind has been recognized for centuries, as the individual strong, manly and very expressive. Lie to a woman has been seen as the big hit of the patriarchal social system. However, this means that today ( in a society that moves to gender equality and equal conditions for all human beings regardless of their gender ) these , women, do be seen as the weaker party in the relationship when in many cases it may not be so? This research was presented in order to recognize and build through the symbols of new masculinities in the city of Armenia, for it is worked under the tenets of Murguialday Clara (2006 ), Flavia A. Limone Reina (2005 ) , Magdalena León de Leal ( 1997 ) Enrique Jimeno (2007 ), Carl Gustav Jung ( 2009 ) and others who have worked on the issues and research involving categories. The target population with which they worked, were men between 30 and 50 years old. To do this, the findings indicate that these men mostly do not recognize the term of the new masculinity, however consider that due to the liberation of women and the sexual revolution, they, like men have been uprooted from stigmas and that the same woman has given them for many decades. Similarly consider the construction of new symbols masculinities more than objects as such, is transferred to behaviors that can adopt and express thanks to the empowerment of women.